2020
DOI: 10.1038/s41598-020-75672-8
|View full text |Cite
|
Sign up to set email alerts
|

Hounsfield unit attenuation value can differentiate pyonephrosis from hydronephrosis and predict septic complications in patients with obstructive uropathy

Abstract: We aimed to assess the role of computerized tomography attenuation values (Hounsfield unit—HU) for differentiating pyonephrosis from hydronephrosis and for predicting postoperative infectious complications in patients with obstructive uropathy. We analysed data from 122 patients who underwent nephrostomy tube or ureteral catheter placement for obstructive uropathy. A radiologist drew the region of interest for quantitative measurement of the HU values in the hydronephrotic region of the affected kidney. Descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Contrast layer inversion, representing contrast material overlying purulent fluid, is rarely encountered. Gas in the collecting system, in the absence of previous procedures, is the most accurate indicator of the presence of the infected fluid [ 28 , 29 , 30 , 33 , 34 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Contrast layer inversion, representing contrast material overlying purulent fluid, is rarely encountered. Gas in the collecting system, in the absence of previous procedures, is the most accurate indicator of the presence of the infected fluid [ 28 , 29 , 30 , 33 , 34 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT signs of pyonephrosis are considered indirect; in fact, in addition to features of obstruction, CT may demonstrate thickening of the renal pelvic wall (>2 mm), parenchymal or perinephric inflammatory changes, dilatation and obstruction of the collecting system, and gas–fluid or fluid–fluid levels in the intrarenal collecting system [ 28 , 29 , 30 , 31 ]. A caveat of CT evaluation is that it is often difficult to distinguish simple hydronephrosis from pyonephrosis by fluid attenuation measurements, although recent studies have demonstrated that patients with pyonephrosis had higher Hounsfiled Units (HU) levels in the dilated collecting system than in the case of simple non-complicated hydronephrosis, supporting its utility in measuring the density of urine in those patients [ 29 , 30 , 31 ]. This may be especially important in patients that cannot undergo contrast-enhanced CT.…”
Section: Ctmentioning
confidence: 99%
See 3 more Smart Citations